Chemical, biological, radiological, and nuclear mass casualty medicine: a review of lessons from the Salisbury and Amesbury Novichok nerve agent incidents. (February 2022) - Haslam, James D.; Russell, Paul; Hill, Stephanie; Emmett, Stevan R.; Blain, Peter G.
Summary: On March 4, 2018, two casualties collapsed on a park bench in Salisbury, Wiltshire, UK. They were later discovered to have been the victims of an attempted murder using the Soviet-era Novichok class of nerve agent. The casualties, along with three further critically ill patients, were cared for in Salisbury District Hospital's Intensive Care Unit. Before the COVID-19 pandemic, the Salisbury and Amesbury incidents were the longest-running major incidents in the history of the UK National Health Service. This narrative review seeks to reflect on the lessons learned from these chemical incidents, with a particular focus on hospital and local organisational responses.